lnflorescence Morphology, Pollination, Fruitset, Dispersal and Establishment Processes o f Aridarum borneense (M.Hotta) Bogner & A.Hay in the Santubong Peninsular - Lee, Mee Chea (Universiti Malaysia Sarawak (UNIMAS), 2007)
Aridarum bOrnel?NSI? (M.Hatta) Bogner & A.Hay IS an obli gate rheophytic species or Araceae tribe Sch isma toglottideae endemic to Sarawa k, Malaysian Borneo. 1l1is field study produced reliabl e results on pollinatIon, fruitset, seed dispersal, seedlulg establishment and inflorescence morphology of A borneense, subsequently enhanced understanding on the adaptations and charac terisllcs of rheophytes. Field work was carried out at Camp Permai on the Saol"ubong Peninsular, at sandstone wClterfall situated at the West Mouth of the Sarawak River, at 110.20E; 1.44N. This area was violent ly mundated by water during periods of heavy rainfall and dried during drought seaSOll. Yet populations of A borneense stil l flourt~h amidst the large sandstone buill up in permanent forest stream. Phe nologica l observa tions were made on spathe opeJl lOgiclosmg. fema le/male anthesis, pollin ator attractant and rewa rds produclioJl (e.g., flora l odours, food-source floral Ilssues, sti gmatic secretions, polle n. e tc.). pollinator, dura tion or vislt and beha viour. f urther observations we re made on seed dispe rsal including dispersa l d istance and seed germinabLli ly, gennllla tion a nd subseq uent seed lin g establishmenL Anth esis lasted for three da ys With no Illsect rrapping mechal11 sm observed . ThermogenesIs and osmophores we re In volved in alrrac tlng insects, and the rewards incl uded starch-rich bod ies &om spadix and spathe. FVldences suggest Chrysornelids (Coleoptera) a~ the prtmary pollinator; however. C%ctlsiom.vlCl (Diptera) might be anolher pollinator of A. borneense. Fruits were matured in eight weeks and dispe"(sed by means of water. As a nature ofrheophytism, the seed ling establishment was very tast., assisted by the fun ction ofmicropyJar appendages.